Study on dust pollution suppression of mine wind-assisted spray device based on orthogonal test and CFD simulation. (15th January 2023) - Nie, Wen; Cha, Xingpeng; Bao, Qiu; Peng, Huitian; Xu, Changwei; Zhang, Shaobo; Zhang, Xu; Ma, Qingxin; Guo, Cheng; Yi, Shixing; Jiang, Chenwang
Abstract: To solve the problem of high-concentration coal dust pollution in a fully mechanized working face, and based on the principle of mechanical wind-assisted negative pressure suction of dust-laden air flow combined with spray dust reduction, a new wind-assisted spray device was investigated. The nozzle of the device was optimized through experimental investigation of the macroscopic characteristics of the spray field. Based on the actual situation of the fully mechanized mining face, a numerical simulation of the wind-assisted spray device was carried out and combined with an orthogonal test. It was shown that when the spray device deviates by 30°, the spray pressure is 6 MPa, and the air output is 90 l/min, resulting in a more efficient spray field. Finally, the wind-assisted spray device was used in the 22, 104 fully-mechanized mining face of Shangwan Coal Mine, China, and the dust concentration was monitored at measuring points before and after the spraying device was switched on. The concentration of total dust and respirable dust at the shearer driver's position decreased to 104.2 mg/m³ and 68.3 mg/m³, respectively, and the dust removal efficiency reached 88.31% and 83.45%, respectively, which effectively suppressed the high-concentration coal dust pollution in the working face. Highlights: Spray dust removal in fully mechanized mining face with large mining height. A kind of wind-assisted spray device installed on coal - shearer was developed. Adopt wind-spray cooperative control and dust removal technology. Reduced the Respirable dust concentration by 83.45%.